Achieving Sex-Representative International Court Benches. Issue 1 (January 2016) - Grossman, Nienke
Abstract : Twenty-five years ago, in this Journal, Hilary Charlesworth, Christine Chinkin, and Shelley Wright argued that the structures of international law "privilege men." As shown in Table 1, which summarizes data from a forthcoming article, on nine of twelve international courts of varied size, subject-matter jurisdiction, and global and regional membership, women made up 20 percent or less of the bench in mid 2015. On many of these courts, the percentage of women on the bench has stayed constant, vacillated, or even declined over time. Women made up a lower percentage of the bench in mid 2015 than in previous years on two-thirds of the courts surveyed.